A fuzzy-PID based control approach for precision volume filling in nitroglycerin production - Yaqin, Sa’id A’inul; Rusli, Mochammad; Siswojo, Bambang (Politeknik Negeri Lhokseumawe, 2025)
The production of nitroglycerin demands highly accurate liquid volume filling, as any deviation can significantly impact both product quality and safety. Peristaltic pumps are employed in this process due to their ability to deliver fluids with precision; however, maintaining volume accuracy amidst process variability remains a major challenge. This study aims to enhance volume-filling accuracy, improve system response, and increase energy efficiency in the nitroglycerin production process by implementing a Fuzzy-PID control system. The Fuzzy-PID method is applied to address uncertainties and dynamic variations inherent in peristaltic pump operations. The system's performance is evaluated in terms of accuracy, response characteristics, and energy consumption. Experimental results demonstrate that the use of Fuzzy-PID control achieves a volume-filling accuracy of up to 98%. This improvement contributes significantly to the efficiency and safety of nitroglycerin production, ensuring higher product quality and operational reliability.